Application Sof Infrared Rays And Desigining A System For Controlling Infrared Rays System (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Infrared rays have many applications in our life and in home applications. Remote control for TVs, air conditioner and other home applications are just several examples, but there are many more applications in manufacturing and in industrial production and factories. This paper uses mainly description, qualitative analysis and analytical and synthesis methods. It is necessary for factories, experts, engineers to set up and design a system for controlling infrared rays. We need to control both release of infrared rays and collection of infrared rays and through its operation. Also a risk management system need to be set up for controlling bad effects from infrared rays release and collection. Our results can be used to advise to set up or design a control system for infrared rays.